The effect of continuous electronic fetal monitoring on mode of delivery and neonatal outcome among low-risk laboring mothers at Debre Markos comprehensive specialized hospital, Northwest Ethiopia - Tirusew Nigussie Kebede; Kidist Ayalew Abebe; Moges Sisay Chekol; Tebabere Moltot Kitaw; Muhabaw Shumye Mihret; Bezawit Melak Fentie; Yared Alem Sibhat; Michael Amera Tizazu; Solomon Hailemeskel Beshah; Birhan Tsegaw Taye (Frontiers Media S.A., 2024)
BackgroundElectronic fetal heart rate monitoring (EFM) has been widely used in obstetric practice for over 40 years to improve perinatal outcomes. Its popularity is growing in Ethiopia and other sub-Saharan African countries to reduce high perinatal morbidity and mortality rates. However, its impact on delivery mode and perinatal outcomes in low-risk pregnancies remains controversial. This study aimed to assess the effect of continuous EFM on delivery mode and neonatal outcomes among low-risk laboring mothers at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia.MethodsA prospective follow-up study was conducted from November 20, 2023, to January 10, 2024. All low-risk laboring mothers meeting the inclusion criteria were included. Data were collected via pretested structured questionnaires and observation, then analyzed using Epi-data 4.6 and SPSS. The incidences of cesarean delivery and continuous EFM were compared using the chi-squared test and Fisher's exact test.ResultsThe study found higher rates of instrumental-assisted vaginal delivery (7% vs. 2.4%) and cesarean sections (16% vs. 2%) due to unsettling fetal heart rate patterns in the continuous EFM group compared to the intermittent auscultation group. However, there were no differences in immediate neonatal outcomes between the groups.ConclusionWhen compared to intermittent auscultation with a Pinard fetoscope, the routine use of continuous EFM among low-risk laboring mothers was associated with an increased risk of cesarean sections and instrumental vaginal deliveries, without significantly improving immediate newborn outcomes. However, it is important to note that our study faced significant logistical constraints due to the limited availability of EFM devices, which influenced our ability to use EFM comprehensively. Given these limitations, we recommend avoiding the routine use of continuous EFM for low-risk laboring mothers to help reduce the rising number of operative deliveries, particularly cesarean sections. Our findings should be interpreted with caution, and further research with adequate resources is needed to draw definitive conclusions.